A criterion to identify the equilibration time in lipid bilayer simulations - Porasso, Rodolfo Daniel (2012)
With the aim of establishing a criterion for identifying when a lipid bilayer has reached steady state using the molecular dynamics simulation technique, lipid bilayers of different composition in their liquid crystalline phase were simulated in aqueous solution in presence of CaCl 2 as electrolyte, at different concentration levels. In this regard, we used two different lipid bilayer systems: one composed by 288 DPPC (DiPalmitoylPhosphatidylCholine) and another constituted by 288 DPPS (DiPalmitoylPhosphatidylSerine). In this sense, for both type of lipid bilayers, we have studied the temporal evolution of some lipids properties, such as the surface area per lipid, the deuterium order parameter, the lipid hydration and the lipid-calcium coordination. From their analysis, it became evident how each property has a different time to achieve equilibrium. The following order was found, from faster property to slower property: coordination of ions ≈ deuterium order parameter > area per lipid ≈ hydration. Consequently, when the hydration of lipids or the mean area per lipid are stable, we can ensure that the lipid membrane has reached the steady state.